Respuesta :

Answer:

[tex]f(x) = 3x^2[/tex] and [tex]g(x) = x + 2[/tex]

Step-by-step explanation:

Given

[tex]h(x) = 3(x+2)^2[/tex]

[tex]h(x) = (fog)(x)[/tex]

Required

Find possible expressions for f(x) and g(x)

[tex]h(x) = (fog)(x)[/tex]

This can be rewritten as:

[tex]h(x) = f(g(x))[/tex]

Recall that [tex]h(x) = 3(x+2)^2[/tex]

So;

[tex]h(x) = f(g(x)) = 3(x+2)^2[/tex]

[tex]f(g(x)) = 3(x+2)^2[/tex]

By comparison, the expression in bracket represents g(x);

Hence;

[tex]g(x) = x + 2[/tex]

Replace g(x) with x

[tex]f(x) = 3(x)^2[/tex]

[tex]f(x) = 3x^2[/tex]

Hence, the possible expressions of f(x) and g(x) are:

[tex]f(x) = 3x^2[/tex] and [tex]g(x) = x + 2[/tex]